A CYBER-TERRORISM AS A THREAT TO NATIONAL SECURITY - Kalac, jasmin (International Scientific Journal Vision, 2019)
The tremendous achievements and the development of the leading technology, sophisticaled computer systems opened new “cyberspace” that constantly destroys the old traditional forms of organization, behavior and belief. Cyber information led to cyber revolution and the emergence of the information society, which dominates the race for information and communication technologies, in parallel the global liberalization and free circulation of people, goods and ideas (Stern, Jessica, 1999). Today, thirty years after the introduction of the term, the concept of cybernetics, it inevitably became a primary component of many important terms: cyber society, cyber policy, cyber economy, cyber warefare, cyber terrorism, cyber crime, in which essentially the most precious crown represents cyber information. Cyber terrorism is an important cybersystem of cyber warefare, and is very difficult to detect and counter because it is almost impossible to determine the political affiliation or sponsors of its prepertators.